Behavioral responses to subsidies in risky investment decisions and the effectiveness of tax credits and grants - Hagen Ackermann; Martin Fochmann; Rebecca Temme (Arbeitskreis Quantitative Steuerlehre (arqus), 2018)
We provide evidence that subsidy types that are identical in monetary terms differ in their behavioral responses and consequently in their effectiveness. In particular, we observe that investments into a subsidized asset are higher under tax credit than under grant. Both subsidy types are essentially very similar, only the mechanism of the subsidy application is different. In case of a grant, an individual gains an amount of money. In case of a tax credit, no money is received directly, but the tax to be paid is decreased by the amount of the tax credit. Our results indicate that these mechanisms have a substantial impact on the effectiveness of subsidies. Applying our findings, governments can "nudge" the investors to support desired investment decisions by using a certain subsidy type. Particularly, our results suggest that when policymakers are indifferent froma budget perspective between providing a subsidy as a grant or as a tax credit, they should implement a tax credit.
Keywords: C91; D14; H24; 330; behavioral taxation; subsidy; risk-taking behavior; prospect theory